DEVELOPMENT OF A MOBILE ROBOTIC SIMULATOR - KELLY, KEVIN (My University, 2012)
Robotic simulators facilitate design a nd testing of robotic platforms. For the purpose of rapid development and edu cation, currently available simulation packages can be overly complex and time consuming for the purpose of rapid development and education. The aim of th is work reported here was to develop a robotic simulator that would address these issues. The programming language python was chosen for its ease of use, readability, and rapid development pedigree. Third party software libraries were used develop the simulator; wxPython - a library for building graphical user interfaces; Pygame - a library used for 2d image rendering and user interaction. The simulator in its current stat e provides good functionality for the testing, development and validation of robotic control systems. Using the developed robotic simulator it is possible to simulate simple worlds, test the performance of robotic control algorithms, graphically visualise simulations in 2d, and perform probabilistic mapping.
29th International Manufacturing Conference
PUBLISHED
Belfast, Ireland
Keywords: Robotic; Simulation